Coming together is a beginning: The making of an intervertebral disc. Issue 1 (27th March 2014) - Chan, Wilson C. W.; Au, Tiffany Y. K.; Tam, Vivian; Cheah, Kathryn S. E.; Chan, Danny
Abstract : The intervertebral disc (IVD) is a complex fibrocartilaginous structure located between the vertebral bodies that allows for movement and acts as a shock absorber in our spine for daily activities. It is composed of three components: the nucleus pulposus (NP), annulus fibrosus, and cartilaginous endplate. The characteristics of these cells are different, as they produce specific extracellular matrix (ECM) for tissue function and the niche in supporting the differentiation status of the cells in the IVD. Furthermore, cell heterogeneities exist in each compartment. The cells and the supporting ECM change as we age, leading to degenerative outcomes that often lead to pathological symptoms such as back pain and sciatica. There are speculations as to the potential of cell therapy or the use of tissue engineering as treatments. However, the nature of the cells present in the IVD that support tissue function is not clear. This review looks at the origin of cells in the making of an IVD, from the earliest stages of embryogenesis in the formation of the notochord, and its role as a signaling center, guiding the formation of spine, and in its journey to become the NP at the center of the IVD. While our current understanding of the molecular signatures of IVD cells is still limited, the field is moving fast and the potential is enormous as we begin to understand the progenitor and differentiated cells present, their molecular signatures, and signals that we could harness in directing the appropriate in vitro and in vivo cellular responses in our quest to regain or maintain a healthy IVD as we age. Birth Defects Research (Part C) 102:83–100, 2014. © 2014 Wiley Periodicals, Inc.